The Impact of Decision Support Systems (DSS) on Employee Work Effectiveness: A Case Study of Telco 2 Segment 3 Operations at PT. Infomedia Nusantara - Fahlevi, Noval; Mahdiana, Deni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines the impact of decision support systems (DSS) on employee work effectiveness at PT Infomedia Nusantara. The study employs a quantitative causal design, with the research subjects being employees of PT Infomedia Nusantara in Operational Division Telco 2 Segment 3 and the research object being DSS and employee work effectiveness. The research population is all employees on Operational Division Telco 2 Segment 3, totaling 128 people. Data were collected through interviews, document recording, and questionnaires and then analyzed using simple regression analysis. The results of the study show that DSS has a significant influence on employee work effectiveness.